Optimization of Solar Panel Deployment Using Machine Learning - Shoaib Kamal; P. S. Ramapraba; Avinash Kumar; Bikash Chandra Saha; M. Lakshminarayana; S. Sanal Kumar; Anitha Gopalan; Kuma Gowwomsa Erko (International Journal of Photoenergy)
In this work, we proposed a mechanism for topology reconfiguration or optimization of photovoltaic (PV) arrays using machine learning-assisted techniques. The study takes into concern several topologies that includes series parallel topology, parallel topology, bridge link topology, honeycomb topology, and total cross tied. The artificial neural network-based topology reconfiguration strategy allows for optimal working conditions for PV arrays. With this, machine learning-assisted topology reconfiguration or optimal solar panel deployment enables the proposed mechanism to achieve higher degree of testing accuracy precision, recall, and f-measure under standard ideal condition.